New challenges for representative democracy: the changing political space in Western Europe - Nicola Maggini (QOE-IJES)
Globalisation and EU integration have reshaped political alignments in western Europe, with the emergence of new conflicts within a political space still ideologically structured in two dimensions (economic and cultural). However, recent challenger parties appear to question such alleged bi-dimensionality, e.g. combining anti-immigrant stances with progressive views on moral issues. In light of such challenges, the article aims to understand whether citizens’ positions on policy issues can still be interpreted according to latent ideological dimensions, exploring possible differences across distinct party electorates and age groups (young vs. older people). The article analyses the ideological consistency of voters’ issue preferences and the dimensionality of the issue space in seven western European countries through original survey data and scaling techniques. Results show that most citizens (especially young and right-wing voters) take ideologically inconsistent positions on cultural GAL-TAN and economic left-right issues, whereas are quite consistent on immigration and EU issues.